Qualitative properties of solutions of the Neumann problem for a higher-order quasilinear parabolic equation - Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The property of localization of perturbations is proved for a solution of an initial boundary-value Neumann problem in a region $D = Ω x,\quad t > 0$, where $Ω$ is a region in $R^n$ with a noncompact boundary.